The Inferiority Complex of Homunculus in Hiromu Arakawa’s Fullmetal Alchemist - Tania P. Thenady; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This article explores the causes and effects of inferiority complex in a character of a manga created by Hiromu Arakawa, Fullmetal Alchemist. Commonly seen as a child’s play and underestimated by the society of literature, comic book or manga actually has the same quality as those considered as literary arts and stands equally with them. It embraces issues freely without the restriction of social rules and individual or group and uncontaminated by social, personal, or political influences. One of the issues most people think will not be in a comic book is psychology. Started from comparing himself to humans, the main antagonist, Homunculus, suffers from an inferiority complex caused by several factors such as parental attitude, physical defects, and envy. Furthermore, as the effect of suffering inferiority complex, Homunculus develops psychological defenses to ease his inferiorities: compensation and superiority complex. He tries to compensate his inferior feelings by excelling in another area and covers up the inferiorities by striving for superiority and omnipotence.